Post-cracking behaviour of steel fibre reinforced concrete (RILEM Recommendations) - Barros, Joaquim A. O. (2003)
Recently, RILEM TC 162-TDF Committee has proposed a specimen configuration, test procedures and flexural tensile strength parameters to characterize the post-cracking behaviour of the steel fibre reinforced concrete (SFRC). The approach proposed by RILEM is still yet under discussion, mainly, the ability of the flexural tensile strength parameters to simulate the post-cracking behaviour of the SFRC on the verifications to the ultimate and serviceability limit states. Taking the recommendations of the RILEM, the influence of the fibre content, the concrete age, and the percentage of cement replaced by fly ash on the bending behaviour of the SFRC was analysed in the present work. The influence of the fibre distribution on the fracture surface of the specimens was also considered. The experimental campaign was carried out with a cost competitive SFRC developed for industrial pavements. Bending tests with concrete specimens reinforced with conventional bars and steel fibres were also performed for developing a reinforcement system adjusted for panels of industrial pavements heavily loaded. The results obtained are presented and analysed.